2012
DOI: 10.2147/ceor.s36352
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dry eye on work productivity

Abstract: BackgroundThe purpose of this study was to evaluate the impact of dry eye on work productivity of office workers, especially in terms of presenteeism.MethodsA total of 396 individuals aged ≥20 years (258 men and 138 women, mean age 43.4 ± 13.0 years) were recruited through an online survey. Data from 355 responders who did not have missing values were included in the analysis. They were classified into the following four groups according to the diagnostic status and subjective symptoms of dry eye: a definite d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 15 publications
(17 reference statements)
1
70
0
2
Order By: Relevance
“…Uchino et al reported that DED status is associated with lower work productivity and impaired work performance in relatively young VDT users 27) . Productivity is also significantly lower among those with DED: the annual cost of work productivity loss is estimated to be USD 741 per person 28) . For early identification and treatment of DED and its complications, as well as concomitant diseases, regular visits to an ophthalmologist should be promoted.…”
Section: Discussionmentioning
confidence: 99%
“…Uchino et al reported that DED status is associated with lower work productivity and impaired work performance in relatively young VDT users 27) . Productivity is also significantly lower among those with DED: the annual cost of work productivity loss is estimated to be USD 741 per person 28) . For early identification and treatment of DED and its complications, as well as concomitant diseases, regular visits to an ophthalmologist should be promoted.…”
Section: Discussionmentioning
confidence: 99%
“…27-29 Adverse environmental conditions not only contribute to the progression of dry eye disease, they also are a risk factor for developing dry eye disease in those with predisposing characteristics, such as low tear volume. 7 Therapies to blunt the ocular surface response to these adverse conditions are important in improving comfort, quality of life, and productivity in those with dry eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…Among 396 individuals aged ≥20 years, the investigators showed that productivity in the group with self-reported DED was significantly lower than that in the control group (P ‹0.05). The annual cost of work productivity loss associated with DED was estimated to be USD $741 per person 61 . Another cross-sectional, web-based survey administered to 9034 individuals aged ≥18 years using the OSDI and the Work Productivity and Activity Impairment Questionnaire 62 showed work productivity loss was related to the severity of DED.…”
Section: The Economic Impact Of Dedmentioning
confidence: 99%